HOST SPECIFIC MOLECULAR VARIATIONS IN BEMISIA TABACI (G.) AS REVEALED BY USING MITOCHONDRIAL AND RIBOSOMAL MARKER - R. ELLANGO; R. ASOKAN; MAHMOOD, RIAZ (The Bioscan, 2014)
Bemisia tabaci is globally important pest and also vector of Gemini viruses on various economically important crops worldwide. Presently there are lots of debates going on the species status and cryptic nature of this species which is complex as challenging. Therefore, in this study we analysed the genetic diversity of B. tabaci (18 samples collected on various host plants). The diversity analysis was performed using two well known markers such as mitochondrial COI gene and the ribosomal ITS1. The phylogenetic trees were constructed separately for two dataset using Neighbor-Joining method. Our result confirmed presence of four putative species of B. tabaci such as Asia I, Asia II 1, Asia II 5 and Asia II 8 in India. The Asia I genetic group found most widely distributed and shows relatively polyphagus, which has mtCOI consensus sequence identity of 84.32% to 86.76% with Asia II sub groups. Our work has shown the genetic boundary of B. tabaci which helped in understanding host specificity across Karnataka, India.